Effectiveness Of Minimally Invasive Surgical Methods For The Treatment Of Necrotizing Enterocolitis In Premature Infants - Suyundikov, Askerkhan Ravilevich; Zholnina, Maria Petrovna; Khusieva, Leyla Said-Magomedovna; Popova, Darya Dmitrievna; Shiryaeva, Maria Sergeevna; Mammayeva, Zhariyat Bulatovna; Bolatov, Niurislam Kemalovich (Journal of Neonatal Surgery, 2025)
This article presents a study of the efficacy of minimally invasive surgical techniques for the treatment of necrotizing enters colitis in preterm infants. The analysis is based on the results of retrospective and prospective follow-up of a group of patients born with extremely low and very low body weight, in whom the presence of necrotic intestinal lesions was confirmed. The features of pathogenesis, clinical picture and risk factors influencing the severity and course of the disease are considered in the work. Special attention is paid to the analysis of two minimally invasive surgical strategies and their comparison with traditional methods of surgical intervention. Survival rates, recovery period, weight gain rates, complication rates and length of hospitalization are presented. The results of the study demonstrate the advantage of some minimally invasive techniques with timely diagnosis and proper patient selection, which helps to improve prognosis and reduce the risk of unfavorable outcomes.